Isolation and characterization of an algicidal bacterium against the bloom-forming algae raphidophyte Heterosigma akashiwo - Zhang, Zhenzhen (Environmental technology, 2023)
Harmful algae blooms (HABs) have increased in intensity and frequency worldwide, causing negative effects on public health and marine ecosystems. This study isolated and identified the bloom causing species and its associated algicidal bacterium during a phytoplankton bloom in coastal waters of Lianyungang, China. Morphological observations and DNA barcoding analysis indicate that the studied phytoplankton bloom was caused by the raphidophyte Heterosigma akashiwo, and the algicidal bacterium, strain LD-B1, was identified as a species belonging to the genus Pseudoalteromonas. Furthermore, the algicidal effects of strain LD-B1 against H. akashiwo were characterized; revealing strain LD-B1 show strong algicidal activity against H. akashiwo. After 48 h of bacterium culture addition, the algicidal rate reached up to 98.8% with a 1% final volume rate. Moreover, our findings indicate strain LD-B1's extracellular compounds involved in algicidal activity are likely not proteinaceous. These findings indicate that the isolated strain, LD-B1, is a promising algicidal bacterium to control H. akashiwo blooms